The role of 18F‐Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (FDG PET/CT) in assessment of complex invasive fungal disease and opportunistic co‐infections in patients with acute leukemia prior to allogeneic hematopoietic cell transplant. Issue 3 (28th December 2020) - Longhitano, Anthony; Alipour, Ramin; Khot, Amit; Bajel, Ashish; Antippa, Phillip; Slavin, Monica; Thursky, Karin
Abstract: Introduction: Individuals diagnosed with acute lymphoid and myeloid malignancies are at significant risk of invasive fungal and bacterial infections secondary to their marked immunocompromised states with a significant high risk of mortality. The role of metabolic imaging with 18F‐Fluorodeoxyglucose (FDG) Positron Emission Tomography/Computed Tomography (PET/CT) has been increasingly recognized in optimizing the diagnosis of invasive infection, monitoring the response to therapy and guiding the duration of antimicrobial therapy or need to escalate to surgical intervention. Methods: Two distinct cases of pulmonary co‐infection of rare fungal and bacterial pathogens are explored in severely immunocompromised individuals where FDG PET/CT aided both patients to make a full recovery and transition to HCT. The first case explores mixed Scedosporium apiospermum and Rhizomucor pulmonary infection on a background of T cell/myeloid mixed phenotype acute leukemia ultimately warranting long‐term antifungal therapy and lobectomy prior to HCT. The second case explores Fusarium and Nocardia pulmonary infection on a background of relapsed AML also warranting surgical resection with lobectomy and long‐term antimicrobials prior to transition to HCT. Discussion: The cases highlight the utility of FDG PET/CT to support the diagnosis of infections, including the presence or absence of disseminated infection, and to provide highly sensitive monitoring of the infection over time. FDG PET/CT played a key role in directing therapy duration decisions and prompted the necessity for surgical intervention. Ultimately, the use of FDG PET/CT allowed for a successful transition to HCT highlighting its value in this clinical setting. Conclusion: FDG PET/CT has an emerging role in the diagnostic and monitoring pathway for complex infections in high‐risk immunocompromised patients.